Cardiovascular risk factors profile in patients with acute coronary syndrome with particular reference to left ventricular ejection fraction - Sheeren Khaled; Rajaa Matahen (Indian Heart Journal, 2018)
Background: Acute coronary syndrome (ACS) remains a leading cause of death in the United States. Numerous studies have shown that the degree of LV systolic dysfunction is a major if not the most important determinant of long-term outcome in ACS. Objectives: To identify the most important risk factors and other clinical predictors which might have impact on left ventricular ejection fraction in patients with ACS. Results: The total patients (299) admitted to our center from July, 2015 till December, 2015; with established diagnosis of ACS were classified in to two groups: Group I: 193 patients with impaired LVEF < 40% (64.5%), Group II: 106 patients with LVEF equal or > 40% (35.5%). The patients of group I were significant elderly compared to those of group II (60.9 ± 11.2 vs 56.9 ± 10.6; p = 0.002), had significant history of DM and CKD (66.3% and 31.1% VS 49.1% and 19.8%; p = 0.004 and 0.036 respectively), presented mainly with STEMI- ACS (51.3% VS 28.3% respectively; p < 0.001) with +v cardiac biomarker (troponin) (90.2% VS 66.0%; p < 0.001). Moreover, patients of group I had more significant ischemic MR compared to the patients of group II (24.9% VS 3.8% respectively; p < 0.001) with higher rate of LV thrombus discovered by echocardiography (25.4% VS 1.9%; p < 0.001). Extensive significant CAD disease was observed to be higher among patients of group I (69.4% VS 57.5%; p = 0.039) and those patients treated mainly with PCI revascularization therapy (68.9% VS 52.8%; p = 0.002) compared to patients of group II who mainly treated medically (34.9% VS 17.6 %; p < 0.001). Multiple logistic regression analysis demonstrated that DM (odd ratio (OR): 2.64, 95% confidence interval (CI): 1.45-4.79, P = 0.01), presence of significant ischemic MR (OR: 13.7, 95% CI:2.84-66.1, p = 0.001)and presence of significantly diseased coronary vessels (odd ratio (OR): 5.06, 95% confidence interval (CI): 1.14-22.6, P = 0.033,) all were independent predictors for significant LV dysfunction (LVEF < 40%) which predict poor outcome in ACS patients. Conclusion: We concluded that DM, presence of significant ischemic MR, and increased number, severity of diseased coronaries all were independent predictors of LV dysfunction (LVEF < 40%) which is known to predict poor outcome. Identification of those risk predictors upon patient evaluation could be helpful to identify high risk-patients, in need of particular care, aggressive therapy and close follow-up to improve their poor outcome.